Pronacera Therapeutics. From the Company to the Scientific Entrepeneurship's or vice versa - Martínez Lara, Antonio; Cotán Marín, David; Sánchez Alcázar, Jose A. (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2016)
Motivation: Focused on unusual clinical analysis serving the personalized requirements of people with rare diseases. Pronacera Therapeutics focuses its activity in rare diseases. The Company is constituted by a multidisciplinary team with a marked experience in apoptosis, mitochondrial and lysosomal diseases. Our company’s vision is not an impediment to also let us to make the most of possible products or leading and high market value services which appear on our daily research activity. Thus the Pronacera pipeline has a full branch of products and services which are the result of the technology transfer of the patentable products of the researchers group's with wich Pronacera has a collaboration agreement to achieve the launching of its technologies into the market. The main goal of this session is to show a REAL aproximation of your future expectatives inside the biotech sector in Spain and around the World through Pronacera Therapeutics and my own expirience.